2017
DOI: 10.1021/acsami.7b02398
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanoclay Suspension for Printing-Then-Solidification of Liquid Materials

Abstract: Additive manufacturing (AM) enables the freeform fabrication of complex structures from various build materials. The objective of this study is to develop a novel Laponite nanoclay-enabled "printing-then-solidification" additive manufacturing approach to extrude complex three-dimensional (3D) structures made of various liquid build materials. Laponite, a member of the smectite mineral family, is investigated to serve as a yield-stress support bath material for the extrusion printing of liquid build materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
194
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(205 citation statements)
references
References 32 publications
5
194
0
Order By: Relevance
“…As a result, the NIPAAm solution has poor extrudability and cannot be used alone for extrusion-based printing applications. Figure 3b-1 and b-2 shows the extrusion process of the Laponite nanoclay suspension, a Bingham plastic material with the unique yield-stress property [12,13,25,26] a nozzle, the Laponite nanoclay suspension in the nozzle is sheared and behaves as a shear thinning fluid material. If the applied stress is higher than its shear yield stress, it behaves like liquid; otherwise, it behaves like solid.…”
Section: Effects Of Nanoclay On Extrudabilitymentioning
confidence: 99%
“…As a result, the NIPAAm solution has poor extrudability and cannot be used alone for extrusion-based printing applications. Figure 3b-1 and b-2 shows the extrusion process of the Laponite nanoclay suspension, a Bingham plastic material with the unique yield-stress property [12,13,25,26] a nozzle, the Laponite nanoclay suspension in the nozzle is sheared and behaves as a shear thinning fluid material. If the applied stress is higher than its shear yield stress, it behaves like liquid; otherwise, it behaves like solid.…”
Section: Effects Of Nanoclay On Extrudabilitymentioning
confidence: 99%
“…This bulk support material could successfully support every feature of a printed part when the yield stress of the support material is higher than surface tension and gravitational forces. Then, the whole liquid structure is solidified in situ by applying suitable cross-linking mechanisms [74,75]. Hinton et al [76] demonstrated a new method of 3D printing polydimethylsiloxane (PDMS) using a hydrophilic Carbopol support bath.…”
Section: Support Bathsmentioning
confidence: 99%
“…Embedded printing techniques overcome challenges in traditional printing methods by utilizing self‐healing materials as support baths (Table ). These fabrication techniques, compatible with a range of bioprinting platforms, also increase material compatibility of extrusion fabrication systems and enhance the resolution and complexity of fabricated constructs . Generally, the approach involves the extrusion of one material into the support bath, stabilization of the material (either the printed material or support), and then washing of the unstable material.…”
Section: Advanced 3d Printing Technologiesmentioning
confidence: 99%